Logistics of Tourist Destination - Edna Mrnjavac (Promet - Traffic&Transportation, 1970)
In tourist destinations, during tourist season, the numberof inhabitants multiplies by several times causing qualitativeand quantitative changes in products and se1vices demand.Transport requirements for greater quantities of goods, whosestructure has been modified, affect the organisation and commercialbusiness of transport enterprises. They have to providefor enlarged transport capacities of suitable structure.The consequence of higher transport demand, derived fromtourist demand consists in better using of transport infrastructuretraffic capacity towards tourist destinations and within itselfIn order to enable visitors to enjoy all the elements of touristoffer, the optimisation of goods, people, information and energyflows within tourist destination and towards it, is indispensable.An optimal tourist offer in a tourist destination is possibleonly if logistics approach is implemented that will lead to awell-organised and functioning system of goods, people, informationand energy flows.